METHODS OF FORMATION OF ADOLESCENTS' SOCIALLY ACTIVE LIFE POSITION (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The given article provides the results of the research of teenagers socialization process in informal youth organizations. The research showed that the most effective methods working with teenagers are following: among pedagogical methods – the methods of consciousness formation, methods of activity organization, methods of stimulating activity, self-education method; among psychological methods – psychodiagnostic methods, psychotherapeutic methods, psycho-correction methods, psychological counseling and sociological methods – observation, survey methods, methods of document analysis, biographical method, expert evaluation; and methods of social work – social analysis, social street work, peer-to-peer method.All of them aimed at the personality development of a teenagers-informal, stimulate their inner activity, self-knowledge, self-development and it is a prerequisite for the development of their social activity.
Keywords: teenager, socialization, informal associations, forms and methods of work with adolescents, directions of improvement of socialization of adolescents.